The effect of the professional self-organization on the formation of professional pedagogical professionalism of future teachers (Pedagogy of Higher and Secondary Education, 2014)
Dudnik N. Yu. The effect of the professional self-organization on the formation of professional pedagogical professionalism of future teachers.The article considers some theoretical approaches to defining the notion of «pedagogical professionalism». It also provides the influence of professional self-organization on the development of future teachers’ professionalism. The comparison of content of such concepts as «professional self-organization» and «self-organization of professional activity» is given.
Keywords: pedagogical professionalism; professional self-organization; self-organization of professional activity; future teachers